Impact of Micro Credit Program on Social Mobility of Women - Prasai, Dilli R (Researcher: A Research Journal of Culture and Society, 2013)
The term development is defined various ways by different social scientist. For an example: Hugo Slim defines it, as "Development is not a commodity to be weighted or measured by gross national products. It is the process of change that enables to take changes of their own destinies and realize their full potential. It requires building up the confidence among the people. For this, the skill, assets and freedoms are necessary conditions to achieve this goal". The process of development crosses number of turns and bends as we see its historical tracks. Its starting point can be considered from mercantilism. The state led strategy is followed as an alternative option of mercantilism. Since the decade of 90, the community-based strategy has become one of the best options. In the later day, the NGO-led strategy is also standing as a strong alternative option in the development arena. It is quite impossible to distinctly differentiate the strategy wise policy of any government but the development by mobilizing the NGO came to be indispensable in the present world. The involvement of the women fluctuates in its dimension. At present, the government/donors and some INGOs and the women-specific National-level NGOs have moved faster to the development adopting gender approach-GAD. Other civil society institutions such as media and trade unions, local NGOs seem still to be grappling with the WAD approach. DOI: http://dx.doi.org/10.3126/researcher.v1i1.8371 Researcher: A Research Journal of Culture and Society Vol.1(1) 2013